SPD Scientific Roadshow: Cell culture 2024 / Nur Fathiah Mohd Radzi and Gurmeet Kaur Surindar Singh - Mohd Radzi, Nur Fathiah; Singh, Gurmeet Kaur Surindar (Faculty of Pharmacy, 2024)
he Tissue Culture Unit, Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Puncak Alam, in collaboration with SPD Scientific (M) Sdn Bhd, organised an engaging SPD Scientific Roadshow on Cell Culture on 26th September 2024. The event was participated by over 50 postgraduates, researchers, lecturers, and cell culture experts from various faculties and institutes. The event successfully combined education, innovation, and networking, creating a valuable platform for knowledge exchange and industry collaboration.